Rancang Bangun Sistem Monitoring Rental Sepeda Berbasis Iot Dan Android - Somantri, S; Insany, Gina Purnama; Novianti, Ane (STIKOM Tunas Bangsa Pematangsiantar, 2024)
In today's sophisticated era, bicycle rental is a popular transportation solution in many cities, and bicycle rental has become part of today's business. Recording user data is still done manually/conventionally, calculating rental time, total rental costs, knowing the coordinates of the location of the bicycle being rented. Based on this description, an IoT and Android-based bicycle rental monitoring system was created. Bicycle rental monitoring system to monitor the whereabouts of rental bicycles such as location coordinates connected to the Firebase server. The system was created using an Arduino Uno microcontroller, RFID MRC522, Wemos ESP 8266, and GPS Neo 6M. The RFID card functions as a registered user ID, when the RFID tag is read by the RFID reader, the Wemos ESP8266 must be connected to WiFi so that the recorded coordinates of the GPS Neo 6M will be sent to the server, as well as the registered user, rental date , rental time, rental costs can be seen in real-time in Firebase, can be seen in the Android application that has been connected to the tool. In this way, it can help bicycle rentals in monitoring the bicycles they rent, as well as processing this rental data so that it is not manual